Analisis Konsep Harta dalam Akuntansi Syariah Berbasis Kepemilikan, Etika Pengelolaan, dan Tanggung Jawab Sosial Islam - Ameliya Saputri; Nur Ain; Masyhuri Masyhuri (Journal of Economics, Management, and Accounting, 2026)
The concept of wealth has a central position in Islamic accounting because it not only represents economic assets but also a trust that contains moral, social, and spiritual dimensions. This article aims to analyze the concept of wealth in Islamic accounting by emphasizing the integration of three main pillars, namely ownership, management ethics, and Islamic social responsibility. This study uses a descriptive qualitative approach based on a literature review of muamalah fiqh, Islamic economics, Islamic accounting standards (AAOIFI and PSAK Syariah), as well as classical and contemporary scientific articles. The results of the study show that ownership of wealth in Islam is relative and functional, where humans act as managers (khalifah), while absolute ownership belongs to Allah SWT. This concept requires the management of wealth based on sharia ethics, such as trust, honesty, justice, transparency, and avoidance of usury, gharar, and maysir practices. In addition, Islamic social responsibility is an inherent element in the concept of wealth, which is manifested through the obligations of zakat, infaq, sadaqah, waqf, and social disclosure based on Islamic Social Reporting (ISR). The findings of this study confirm that sharia accounting is not solely oriented towards achieving material profits, but is directed towards achieving benefits, blessings, and accountability to Allah SWT and society.